Ethical dilemmas in global mental health - Cherepanov, Elena (BJPsych Int, 2019)
Global mental health (GMH) work reminds us about our professional ideals and mission. GMH specialists conduct research and provide psychosocial and mental health support to populations affected by humanitarian crises around the world. This work exposes these specialists to situations with a high degree of moral ambiguity and no good solutions, where humanitarian accountability takes priority over conflicting values. Self-awareness helps to address the countertransference that confounds complex decision-making and can compromise the health and safety of all involved. The evolving role of GMH as a humanitarian actor underscores the importance of professional competencies in assuring the integrity and standards of practice.